REFORM OF VOCATIONAL EDUCATION IN CHINA (EFFECT FOR CHINA’S ECONOMIC GROWTH) - Ping Zhao Muhammad Aris Ichwanto (ISSN 0852-2480)
Abstract: Nowdays, the guideline of education reform in China is the official document: National Plan for Medium and Long-term Education Reform and Development. This plan started 2010 and is supposed to direct education reform in China until 2020. Since the plan has been implemented,this article is going reviewed national document’s to portrait the vocational education reform in China nowdays and evaluate the impact on economic development of the implementation of vocational education.At the end of 10th five-year plan, the rural students enrolled in secondary vocational school will reach 3.5 million. These schools will cultivate practical talents for rural areas in China. Reform in vocatinal education in China has significantly influece on China’s economic growth, specially on agriculture and industries sectors.Keywords: reform, vocational education, economic growth